2021
DOI: 10.1186/s12872-021-02177-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification and mortality prediction in octo- and nonagenarians with peripheral artery disease: a retrospective analysis

Abstract: Objectives Among changes in demographics, aging is the most relevant cardiovascular risk factor. The prevalence of peripheral artery disease (PAD) is high in elderly patients and is associated with a worse prognosis. Despite optimal treatments, mortality in the high-risk population of octo- and nonagenarians with PAD remains excessive, and predictive factors need to be identified. The objective of this study was to investigate predictors of mortality in octo- and nonagenarians with PAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This underlines the extent of risk associated with developed PAD [14]. On the other hand, in the group with ABI ≥ 0.9, not only the classic risk factors such as age, male sex, smoking, higher SBP, but also the levels of IL-6 and NT-proBNP increased the risk of death which is in line with the results of earlier studies [20][21][22][23][24]. This may indicate a potential role of inflammageing and subclinical circulatory failure as clinical modifiers of PAD [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…This underlines the extent of risk associated with developed PAD [14]. On the other hand, in the group with ABI ≥ 0.9, not only the classic risk factors such as age, male sex, smoking, higher SBP, but also the levels of IL-6 and NT-proBNP increased the risk of death which is in line with the results of earlier studies [20][21][22][23][24]. This may indicate a potential role of inflammageing and subclinical circulatory failure as clinical modifiers of PAD [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Another study investigated the factors that influence the risk of death in PAD patients over the age of 80 and 90 years [ 113 ]. One-year mortality was 25% (35/123 patients) above the age of 80 years compared to 10% (13/123 patients) in the group of patients under the age of 80 years.…”
Section: Epidemiology Risk Factors and Clinical Course Of Atheroscler...mentioning
confidence: 99%
“…One-year mortality was 25% (35/123 patients) above the age of 80 years compared to 10% (13/123 patients) in the group of patients under the age of 80 years. In the group of PAD patients aged 80 years and above, it was found that the concentration of cardiovascular markers such as troponin > 40 ng/L (HR: 4.6; 95% CI: 1.4–15.3) and NT-pro-BNP > 450 pg/mL (HR: 3.9; 95% CI 1.8–8.8) and the occurrence of MALE (HR: 3.1; 95% CI 1.6–5.9) were strong predictors of patient death [ 113 ]. Features of ischemia, HF, and MALE determine the survival of this group of patients.…”
Section: Epidemiology Risk Factors and Clinical Course Of Atheroscler...mentioning
confidence: 99%
“…According to the Inter-Society Consensus for the Management of Peripheral Arterial Disease (TASC II), CLTI is defined as chronic ischemic rest pain, ulceration or gangrene due to PAD [14]. CLTI is associated with an increased mortality, a high risk of major amputation and impaired quality of life [15][16][17][18]. Frequent complications include infections and gangrene, as well as major amputations.…”
Section: Introductionmentioning
confidence: 99%